2021
DOI: 10.1007/s13300-021-01141-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Use of Once-Weekly Semaglutide in Type 2 Diabetes: Results from the SURE UK Multicentre, Prospective, Observational Study

Abstract: Introduction Once-weekly (OW) semaglutide was associated with clinically relevant improvements in glycaemic control and body weight versus comparators in the SUSTAIN randomised controlled trials (RCTs). SURE UK, which is one of a series of individual studies that comprise the SURE programme, evaluated the use of OW semaglutide in a real-world patient population with type 2 diabetes (T2D) in the UK. Methods In this prospective, observational study, adults (≥ 18 years) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 32 publications
12
18
0
Order By: Relevance
“…Overall, the results of this study support previously reported data on the real-world use of OW semaglutide in Spain [ 39 , 40 , 41 ]. The reduction in HbA 1c and BW observed in Spain align with those observed in the countries that have published results from the SURE programme to date—Canada, Denmark/Sweden, Switzerland, and the UK—for which the mean change in HbA 1c from baseline to EOS was between −0.8 and −1.5%-points and the mean change in BW from baseline to EOS was between −4.3 and −5.8 kg [ 42 , 43 , 44 , 45 ]. The results are also aligned with real-world evidence from other countries, for example, a study by Marzullo et al, that showed reductions in HbA1c and body weight after 6 and 12 months of OW semaglutide treatment in people with T2D in Italy [ 46 ].…”
Section: Discussionsupporting
confidence: 71%
“…Overall, the results of this study support previously reported data on the real-world use of OW semaglutide in Spain [ 39 , 40 , 41 ]. The reduction in HbA 1c and BW observed in Spain align with those observed in the countries that have published results from the SURE programme to date—Canada, Denmark/Sweden, Switzerland, and the UK—for which the mean change in HbA 1c from baseline to EOS was between −0.8 and −1.5%-points and the mean change in BW from baseline to EOS was between −4.3 and −5.8 kg [ 42 , 43 , 44 , 45 ]. The results are also aligned with real-world evidence from other countries, for example, a study by Marzullo et al, that showed reductions in HbA1c and body weight after 6 and 12 months of OW semaglutide treatment in people with T2D in Italy [ 46 ].…”
Section: Discussionsupporting
confidence: 71%
“…The study design and endpoints were similar for all four SURE studies and have been reported elsewhere 21–24. The participating clinics were selected in close collaboration with the Novo Nordisk affiliates in the various countries to ensure representativeness of the local populations.…”
Section: Methodsmentioning
confidence: 99%
“…The results from the first four individual SURE studies to report (CA (n=452),21 DK/SE (n=331),22 CH (n=214)23 and UK (n=215))24 showed that patients receiving OW semaglutide experienced statistically and clinically significant improvements in glycemic control and reduction in body weight. Because of the impact of the coronavirus (COVID-19) pandemic on the timelines of the incomplete SURE studies, as well as the resultant changes to protocols, it was decided to perform a pooled analysis only of the first four available studies.…”
Section: Objectivementioning
confidence: 99%
“…An imbalance in AEs with fatal outcome was observed with semaglutide versus IAsp, which contrasts with previous, extensive data with OW semaglutide from clinical trials, [13][14][15][16][17][18][19][20][21][22] including the CVOT SUS-TAIN 6 22 and real-world data. [38][39][40][41] There was no clustering of causes or any observed pattern regarding the timing of AEs with fatal outcome (Table S8). Deaths primarily occurred in participants with multiple, longstanding pre-existing medical conditions.…”
Section: Author Contributionsmentioning
confidence: 99%